Chad : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2012 Article IV Consultation focuses on Chad's economic developments and policies. Economic performance in 2011-2012 has been marked by an oncoming stream of several large industrial projects. The IMF report highlights that growth slowed in 2011 and inflation accelerated at year's end, while the balance of payments strengthened. The nonoil primary deficit declined in 2011, and the overall fiscal balance swung from a deficit to a small surplus leaving room for private-sector credit expansion. A new approach, developed in collaboration with international partners (including the Food and Agriculture Organisation and World Food Programme), focuses on improving water management, warehouse capacity, and information systems.